Influence of career awareness on STEM career interests among foundation-year students in Mogadishu, Somalia - Abdi, Abdirahman Ibrahim; Mahdi, Abdikarim Osman; Omar, Abukar Mukhtar; Asiimwe, Constance; Osman, Mohamed Ali (Frontiers in Education, 2024)
This study investigates the influence of career awareness on STEM career interests among Foundation-year students in Mogadishu, Somalia. By examining self-efficacy, outcome expectations, and academic performance as mediating factors, the research provides new insights into the complex relationships that shape students' aspirations in STEM fields. Data were collected through a survey of 321 students across four private and public universities and analyzed using Structural Equation Modeling in R-Programming to ensure rigorous evaluation of validity and reliability. The findings reveal that self-efficacy plays a pivotal role in motivating students to pursue STEM careers. At the same time, positive outcome expectations and academic achievements further reinforce their interest in STEM pathways. Although the direct relationship between STEM career awareness and career interests was not statistically significant, the results emphasize the importance of fostering self-belief among students. This study contributes to the understanding of the multifaceted factors influencing STEM career interests and offers practical strategies to enhance self-efficacy, positive outcome expectations, and academic excellence. These findings can inform the development of interventions aimed at inspiring and empowering students in their pursuit of STEM careers.